Kruppel-like factor 2 acts as a tumor suppressor in human retinoblastoma. (March 2022) - Wu, Nandan; Chen, Shuilian; Luo, Qian; Jiang, Zihua; Wang, Xiao; Li, Yan; Qiu, Jin; Yu, Keming; Yang, Ying; Zhuang, Jing
Abstract: Krüppel-like factor 2 (KLF2) belongs to the KLF family of zinc-finger transcription factors and mediates the occurrence and progression of various cancers. However, little is known about its expression pattern and biological role in retinoblastoma (RB). In the present study, we showed that KLF2 was markedly downregulated in human RB tissue compared with retina. KLF2 overexpression significantly inhibited RB cell proliferation and decreased proliferating cell nuclear antigen (PCNA) expression. Subsequently, we confirmed that KLF2 arrested cells at the G1-S phase transition, accompanied by the upregulation of p21 and downregulation of CyclinD1, as well as the activation of mitochondria-mediated apoptosis in RB cells. In addition, KLF2 overexpression contributed to suppressing RB cell migration and invasion by downregulating matrix metallopeptidase 9 (MMP9). On the contrary, KLF2 downregulation promoted RB cells proliferation, migration and invasion. Notably, the KLF2 expression pattern was opposite to that of C-X-C chemokine receptor 4 (CXCR4) in the two RB cell lines, KLF2 overexpression significantly decreased CXCR4 expression, silencing KLF2 had the opposite effect. Furthermore, dual-luciferase reporter and chromatin immunoprecipitation (ChIP) assays confirmed that KLF2 directly bound to the CXCR4 promoter and negatively regulated its expression in RB cells. Collectively, our results suggested that KLF2 function as a tumor suppressor in RB and may represent a potential therapeutic target for RB. Highlights: KLF2 expression is substantially downregulated in RB cells. KLF2 inhibits cell proliferation and promotes cell apoptosis in RB cells. KLF2 overexpression suppresses RB cells migration and invasion. KLF2 downregulation promotes the proliferation, migration and invasion of RB cells. KLF2 binds to the CXCR4 promoter and decreases its expression in RB cells.